CATASTROPHIC MUSCULOSKELETAL INJURIES IN THOROUGHBRED HORSES, CARACAS-VENEZUELA - Morales B., Abelardo (2009)
A clinical and pathological study was conducted on musculoskeletal catastrophic lesions of the locomotive apparatus occurred in 78 Thoroughbred horses in the racetrack «La Rinconada», Caracas, Venezuela, during 2000 to 2007. Blood samples were collected for hematological, biochemical and parathormone analysis in blood. Also, urine samples for phosphate levels. All animals were euthanized due to severe lesions, and bone, tendons, stomach, kidney and liver samples were taken for by histopathology evaluation. Clinical exams revealed lameness grade IV-V in all animals. Losses of bone continuity (fracture) occurred in all cases, and exposition of bone structures, joint damage, rupture of tendons and ligaments and vascular destruction were observed in 60% of them. The types of fractures were comminuted (60%), oblique (25%) and spiral (15%). Blood and urine values were affected. Necropsy showed equine gastric ulcer syndrome, liver congestion and renal acute tubular necrosis. Histopathological analysis showed acute and severe gastritis, gastric ulcers, hepatic periacinar necrosis, osteomalacia and necrosis in subchondral bone, chondromalacia and severe capsulitis.